Kemampuan Siswa dalam Merencanakan Penyelesaian Masalah melalui Pendekatan Matematika Realistik yang Mengintegrasikan Nilai Islami - Jannatul Alyana; Cut Morina Zubainur; Suhartati Suhartati (Universitas Syiah Kuala, 2020)
This study aimed to examine students' abilities in planning problem-solving through a realistic mathematical approach integrating Islamic values in one of the junior high schools in Aceh, Indonesia. This research employed a mix-method approach. The population of this study was all Year 7 students in the school studied (35 students). The sample was one group chosen randomly (7 students). The data were collected through tests of problem-solving abilities and semi-structured interviews. The data were analyzed descriptively by comparing the data from the test results and interviews to describe the ability of problem-solving planning. The results showed that the students' ability of problem-solving planning through a realistic mathematical approach developed for each lesson. In the first lesson, three out of seven students met the ability of problem-solving planning. Furthermore, in the second lesson, five out of seven, and in the third lesson, six out of seven students fulfilled the ability of problem-solving planning. This research implies that teachers can expand the application of a realistic mathematical approach integrating Islamic values to other materials to foster the ability of problem-solving planning.